Awareness of Cervical Cancer and Attitude Toward Human Papillomavirus and Its Vaccine Among Ghanaians - Drokow, Emmanuel Kwateng; Zi, Liu; Han, Qian; Effah, Clement Yaw; Agboyibor, Clement; Sasu, Evans; Akpabla, Gloria Selorm; Foli, Francis; Sun, Kai (Frontiers in Oncology, 2020)
Background: Cervical cancer (CC) is the fourth most commonly diagnosed cancer among women. Ghana is a low-middle- income country with annual diagnosed cases of 3151 and 2119 deaths. The high prevalence rate of cervical cancer in Ghana is mainly due to ineffective preventive measures and insufficient knowledge about the disease. Therefore, our objective was to evaluate the level of knowledge and awareness of cervical cancer and attitude towards human papillomavirus and its vaccine among Ghanaians. Methods: This descriptive cross-sectional survey on the awareness of cervical cancer and attitude towards human papillomavirus and its vaccine was carried out from March 2019 to February 2020. SPSS v. 23.0 was used in the data analysis. The participants' demographic characteristics, knowledge of cervical carcinoma, human papillomavirus vaccine and HPV, and the likelihood to be vaccinated were represented as percentages and frequencies. The difference between males and females was assessed using the chi-square test. The logistic regression analysis was used to evaluate the relationship of possible related indicators with the willingness to receive the HPV vaccine. A p-value < 0.05 was considered statistically significant Results: A total of 1376 participants were involved in the final analysis. Among the 1376 participants involved in this survey, 1240 participants (90.1%) representing 456 males (33.1%) and 784 females (57.0%) were aware of the terminology "cervical cancer" with a significant p-value = 0.001. When stratified by gender, women had significantly greater knowledge, compared to men in terms of “cervical cancer being common in middle age (35-50) females” (75.5% vs. 67.5% respectively, p-value = < 0.001). When stratified by gender, women had significantly greater knowledge of human papillomavirus (54.5% vs. 43.6% respectively, p-value < 0.001) and the human papillomavirus vaccine (39.3% vs. 33.1% respectively, p-value = 0.019) compared to men. Conclusion: Majority of the respondents had poor knowledge regarding cervical cancer risk factors, symptoms, HPV and its vaccine. Hence, this indicates a wakeup call for government to increase the awareness and knowledge level via the media and health professionals.